2018
DOI: 10.2147/ijn.s166104
|View full text |Cite
|
Sign up to set email alerts
|

Novel silk fibroin nanoparticles incorporated silk fibroin hydrogel for inhibition of cancer stem cells and tumor growth

Abstract: BackgroundA multi-drug delivery platform is needed as the intra-tumoral heterogeneity of cancer leads to different drug susceptibility. Cancer stem cells (CSCs), a small population of tumor cells responsible for tumor seeding and recurrence, are considered chemotherapy-resistant and have been reported to be sensitive to salinomycin (Sal) instead of paclitaxel (Ptx). Here we report a novel silk fibroin (SF) hydrogel-loading Sal and Ptx by incorporating drug-loaded silk fibroin nanoparticles (SF-NPs) to simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Despite the fact that the in vitro effectiveness of PTX was not modified by the encapsulation in SFNs, we assume that our nanosystems could improve the cytotoxicity of PTX when in vivo administered. In fact, different authors demonstrated that the use of silk nanoparticles, as anticancer drug delivery systems, can increase the drug accumulation in target cancer tissues and reduce the efflux pump-mediated drug resistance [7,48]. Furthermore, silk fibroin nanoparticles can be functionalized, with the peptide motif RGD (arginine-glycine-aspartic acid), to enhance their interaction with tumor tissues and to reduce side effects [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the in vitro effectiveness of PTX was not modified by the encapsulation in SFNs, we assume that our nanosystems could improve the cytotoxicity of PTX when in vivo administered. In fact, different authors demonstrated that the use of silk nanoparticles, as anticancer drug delivery systems, can increase the drug accumulation in target cancer tissues and reduce the efflux pump-mediated drug resistance [7,48]. Furthermore, silk fibroin nanoparticles can be functionalized, with the peptide motif RGD (arginine-glycine-aspartic acid), to enhance their interaction with tumor tissues and to reduce side effects [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several suitable delivery carriers and systems have been developed. Table 4 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 summarizes recent DDSs for targeting CSC genes and epigenetics.…”
Section: Ddss For Targeting Csc Genes and Epigeneticsmentioning
confidence: 99%
“…Therefore, it is wise to combine conventional anticancer agents and anti-CSC agents for improved therapeutic response 144 , 145 . Recently, many researchers have reported successful development of co-delivery systems for combination therapy ( Table 5 30 , 31 , 73 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ; Fig. 7 30 , 31 ).…”
Section: Ddss For Combination Therapymentioning
confidence: 99%
“…The dual drug-loaded hydrogel had homogeneous drug distribution and exhibited increased tumor inhibition compared to the single drug-loaded hydrogel, as evidenced by fewer CD44 + CD133+ tumor cells in vivo. Because paclitaxel and salinomycin interacted differently with SF, their release profiles were different, with paclitaxel showing sustained release and salinomycin an initial burst release [ 92 ]. Gangrade et al introduced carbon nanotubes into SF hydrogels to construct an on-demand, tumor-targeting system [ 93 ].…”
Section: Applications In Drug Deliverymentioning
confidence: 99%